Fluoride intake from regular and low fluoride dentifrices by 2-3-year-old children: Influence of the dentifrice flavor - Moraes, Samanta Mascarenhas; Pessan, Juliano Pelim [UNESP]; Ramires, Irene; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2007)
This study evaluated the fluoride intake from dentifrices with different fluoride concentrations ([F]) by children aged 24-36 months, as well as the influence of the dentifrice flavor in the amount of fluoride ingested during toothbrushing. Thirty-three children were randomly divided into 3 groups, according to the [F] in the dentifrices: G-A (523 μgF/g), G-B (1,062 μgF/g) and G-C (1,373 μgF/g). Dentifrices A and B are marketed for children, while dentifrice C is a regular product. The amount of F ingested was indirectly obtained, subtracting the amount expelled and the amount left on the toothbrush from the amount initially loaded onto the brush. The results were analyzed by ANOVA, Tukey's test and linear regression analysis (p < 0.05). Children ingested around 60% of the dentifrice loaded onto the brush, but no significant differences were seen among the groups (p > 0.05). Mean daily fluoride intake from dentifrice for G-A, G-B and G-C was 0.022 a, 0.032 a and 0.061 b mg F/kg body weight, respectively (p < 0.01). There was a strong positive correlation (r = 0.86, p < 0.0001) between the amount of dentifrice used and the amount of fluoride ingested during toothbrushing. The results indicate the need for instructing children's parents and care givers to use a small amount of dentifrice (< 0.3 g) to avoid excessive ingestion of fluoride. The use of low-[F] dentifrices by children younger than 6 years also seems to be a good alternative to minimize fluoride intake. Dentifrice flavor did not influence the percentage of fluoride intake.
Keywords: Dental care for children; Dental fluorosis; Dentifrices; Fluorides; anticaries agent; flavoring agent; fluoride; toothpaste; chemistry; clinical trial; controlled clinical trial; controlled study; epidemiology; female; human; male; preschool child; randomized controlled trial; standard; tooth brushing; tooth disease; Cariostatic Agents; Child, Preschool; Epidemiologic Methods; Female; Flavoring Agents; Fluorosis, Dental; Humans; Male; Toothbrushing; Toothpaste